2017
DOI: 10.3390/su9122162
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Gamified Smart Tourism Applications: An Integrative Approach

Abstract: Abstract:Considering that the core concerns in sustainability are threats to the survival of humankind and the ecosystems that humans depend on, changing the consumption and production behaviors of individuals and society is inevitable. However, people are reluctant to change their own behavior in support of sustainability goals. This tendency seems to be especially strong in tourism because the main value of tourism is hedonic utility. Thus, the tourism industry is now introducing gamification and smart touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 92 publications
5
100
1
Order By: Relevance
“…Thus, tourists found that social networks could also serve their information-seeking purposes. However, the results differed from the findings of Yoo et al [38], which found no significant effect on the intention to use. The results may relate to the characteristics of particular media, which conform to the intense information consumption of the industry.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, tourists found that social networks could also serve their information-seeking purposes. However, the results differed from the findings of Yoo et al [38], which found no significant effect on the intention to use. The results may relate to the characteristics of particular media, which conform to the intense information consumption of the industry.…”
Section: Discussioncontrasting
confidence: 99%
“…Information-seeking, relationship maintenance, and entertainment motives had statistical effects on the intention to use SNSs for trips. These results supported the prior findings that entertainment and relationship maintenance motives affected the behavioral intention [38,39,72]. Tourists found that social networks provided them with benefits in terms of entertaining and connecting with people who had a similar interest in traveling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result indicates that the user does not expect high-level game attributes and, thoroughly, high levels of emotional stimuli are not required from an application whose ultimate goal is recycling promotion [23].…”
Section: Discussionmentioning
confidence: 81%
“…However, since both the social and hedonic aspects seem fundamental in an application based on gamification, the extended TAM, as well as the Self-Determination Theory (SDT), have been used to support the hypotheses that will be presented [22]. As Changsok [23] argues, gamification applications in smart tourism have an inherent hedonistic value of game mechanics.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%